PENGARUH PENGGUNAAN INTERNET TERHADAP ADOPSI TEKNOLOGI BUDIDAYA BAWANG MERAH DI LAHAN PASIR PANTAI KABUPATEN BANTUL - Satrio, Anggi Dwi; Witjaksono, Roso; Harsoyo, Harsoyo (Berkala Ilmiah AGRIDEVINA, 2017)
This research was conducted in Sanden subdistrict Bantul district with the purpose offinding out: 1) the use of internet by onion farmers and the factors that affect it, 2) Levelitation the technology adoption of onion cultivation and the factors that affect it,and 3) the influence of the internet use and other factors toward technology adoption ofonion cultivation. The method that used in this research was descriptive approach bysurvey technique. The sampling of village and farming groups were done purposively,while the sampling of respondent farmers were done randomly. The number of totalsample was 60 farmers consisted of 30 farmers from Manunggal Farming Group,Srigading Village, and 30 farmers from Phitisari Farming Group, Gadingsari Village.The analysis methods used were proportion test and multiple linier regressionanalysis. The result of this research showed that the use of internet by farmer’s isbelonged to low category. The education and farmer’s attitude positively affected towardthe use of internet, while age and credibility of internet didn’t have significant affect. Thetechnology adoption of onion cultivation by farmer’s is belonged to high category. Therole of the extension worker and the role of farming group positively affected towardtechnology adoption of onion cultivation. The use of internet and motivation didn’t havesignificant affect toward technology adoption of onion cultivation.